Design and modeling of a 2x2 MEMs optical switch based on electrostatic actuation - 361243 Leow, Cheah Wei; Abu Bakar Mohammad, 1959-; Norazan Mohd. Kassim; IEEE National Symposium on Microelectronics (NSM 2001) (2001 : Genting Highlands) (Skudai : Universiti Teknologi Malaysia, 2001)
16